John F. Kennedy and his role in American politics until 1963 (Journal of the College of Basic Education, 2022)
John Kennedy, the thirty-fifth president of the US presidency (1961-1963) of the Democratic Party, the youngest president secretly of the presidents who took power in the country, and the first Catholic to assume the presidency of the country. Serving in the military and participated in World War II in the South Pacific, and represented the state of Massachusetts from 1947 until 1960 in the Senate. This experience motivated him to enter the presidential race as a candidate for the Democratic Party, and his presidential term witnessed many political tensions, especially with the Soviet Union, and during his rule, exciting events occurred, including the Cuban missile crisis, the Bay of Pigs invasion, the building of the Berlin Wall, and the escalation of the American-Vietnamese war. The pioneer of the launch of the US space program. He also tried to achieve some internal reforms in the country, but he was not successful in implementing them all. The world still remembers and talks about the late President John F. Kennedy after his death than he talked about during his life as John F. Kennedy was killed and assassinated on November 22, 1963 by a young man who was said to be a leftist and was said to be one of the hard-line extremists calling for racial discrimination, or of both. The case of his death is surrounded by suspicion due to different accounts, and is shrouded in mystery and fog.